Convergence of per capita carbon emissions in the Yangtze River Economic Belt, China. Issue 5 (August 2019) - Yu, Shiwei; Hu, Xing; Zhang, Xuejiao; Li, Zhenxi
The convergence of carbon emissions in important regions is a key prerequisite for reaching China's carbon emissions peak target. The Yangtze River Economic Belt (YREB) is the latest strategic economic area in China. In this study, a method of investigating the convergence of per capita carbon emissions in the YREB is proposed, and it includes the following models:σ convergence, stochastic convergence andβ convergence. Besides, the five control variables per capita Gross Domestic Product (GDP), energy consumption structure, industrial structure, population density and urbanization rate are considered in the test models. In addition to testing the whole sample of 74 cities belonging to the Economic Belt, the convergence of three subgroups (municipalities, capital and sub-provincial cities and prefecture-level cities) is also tested by considering spatial effects. The following results are obtained: (1) althoughσ convergence andβ conditional convergence are observed, stochastic convergence is not observed for the 74 cities; (2) the per capita GDP and energy structure are the key factors influencing the cities' convergence, whereas the urbanization rate has a limited impact; and (3) improving the industrial structure and reducing the population density are effective methods of promoting the convergence of per capita carbon emissions among the capital and sub-provincial cities and municipalities, respectively.